Carbazole-benzothiadiazole-based conjugated copolymers : synthesis, electrochromism and electrofluorochrochromism - Ding, Guoqiang (2014)
Two electrochemical reaction-induced chromic phenomena, electrochromism and electrofluorochromism, exhibited by some conjugated polymers (CPs) have been attracting much attention from researchers in recent years. Electrochromism is defined as the reversible change in absorption or transmission of a material due to redox processes induced by an external voltage. Electrofluorochromism is known as reversible change in fluorescence emission induced by applying an electric potential. The electrochromic (EC) and electrofluorochromic (EFC) properties are both related to the redox process of CPs induced by external potential, albeit they are two different types of chromic properties in terms of their work mechanism. The motivation of this work is to explore the structure design of CPs to tune their electrochromic and electrofluorochromic properties, and investigate the underlying mechanism.